2020
DOI: 10.1371/journal.pone.0229589
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and antimicrobial activity of endophytic fungi isolated from Securinega suffruticosa in the Yellow River Delta

Abstract: Securinega suffruticosa (Pall.) Rehd is an excellent natural secondary shrub in the Shell Islands of Yellow River Delta. The roots of S. suffruticosa have high medicinal value and are used to treat diseases, such as neurasthenia and infant malnutrition. Any organism that is isolated from this species is of immense interest due to its potential novel bioactive compounds. In this research, the distribution and diversity of culturable endophytic fungi in S. suffruticosa were studied, and the endophytic fungi with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 53 publications
8
46
0
Order By: Relevance
“…Fungal crude extracts with antibacterial activity were further examined for their MIC and MBC by the agar disc-diffusion assay[ 20 ] against MRSA [ Table 5 ]. EtOAc and MeOH extracts of EF14 had MIC value of 4.80 and 4.90 mg/mL, respectively, though only EtOAc extracts displayed MBC at the concentration of 9.60 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal crude extracts with antibacterial activity were further examined for their MIC and MBC by the agar disc-diffusion assay[ 20 ] against MRSA [ Table 5 ]. EtOAc and MeOH extracts of EF14 had MIC value of 4.80 and 4.90 mg/mL, respectively, though only EtOAc extracts displayed MBC at the concentration of 9.60 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The wilt prevalence in eggplant to an extent of more than 70% was reported to be contained by the formulations of Pseudomonas sp., Enterobacter sp., and Bacillus sp., and it was found that most of these isolates produced an antibiotic DAPG under in vitro conditions [75]. The naturally-occurring bacterial endophytes that could confer a prominent disease resistance to plants are very low in number and such populations have to be raised to a specific level in order to encourage a contrasting check in the proliferation of phytopathogens [76].…”
Section: Discussionmentioning
confidence: 99%
“…The relative frequency (RF) was expressed as the ratio of the number of isolates of a specific taxon to the total number of isolates in each nest. Dominance (Y) was calculated as described by Du et al [50]; a dominant genus was defined when Y > 0.02. The following ecological diversity measures used by Du et al [50] and characterised by Magurran [51] were calculated for each nest: species richness index (S), Margalef index (D ), Shannon-Wiener index (H ), Simpson diversity index (D s ), Simpson dominant index (λ), Pie index (PIE) and Pielou's evenness index (J).…”
Section: Isolation and Identification Of Culturable Fungi From Rch Soils Using The Soil Dilution Methodsmentioning
confidence: 99%